Reviewing the options for local estrogen treatment of vaginal atrophy - Lindahl SH (Dove Medical Press, 2014)
Sarah H Lindahl Sutter East Bay Medical Foundation, SEBMF – Diablo Division, Castro Valley, CA, USA Background: Vaginal atrophy is a chronic condition with symptoms that include vaginal dryness, pain during sex, itching, irritation, burning, and discharge, as well as various urinary problems. Up to 45% of postmenopausal women may be affected, but it often remains underreported and undertreated. This article aims to review the current recommendations for treatment of vaginal atrophy, and current data on the effectiveness and safety of local vaginal estrogen therapies. Methods: Literature regarding vaginal atrophy (2007–2012) was retrieved from PubMed and summarized, with emphasis on data related to the treatment of vaginal atrophy with local vaginal estrogen therapy. Results: Published data support the effectiveness and endometrial safety of low-dose local estrogen therapies. These results further support the general recommendation by the North American Menopause Society that a progestogen is not needed for endometrial protection in patients using low-dose local vaginal estrogen. Benefits of long-term therapy for vaginal atrophy include sustained relief of symptoms as well as physiological improvements (eg, decreased vaginal pH and increased blood flow, epithelial thickness, secretions). Conclusion: Currently available local vaginal estrogen therapies are well tolerated and effective in relieving symptoms of vaginal atrophy. Recent data support the endometrial safety of low-dose regimens for up to 1 year. Keywords: menopause, estrogen, local estrogen therapy, vaginal atrophy